Questioning Research as a Contextual Practice - John Mclntyre; Nicky Solomon (Adult Education Research Conference, 2000)
Authoritative texts on research in adult education rarely question how research practice is shaped by its context of application. This paper attempts to develop a knowledge production perspective on research as contextualised practice, one that highlights the relationship between researcher understandings and the situations, participants, processes and texts of research.